Black Time and the Aesthetic Possibility of Objects. - Lamothe, Daphne (Chapel Hill : University of North Carolina Press, 2024)
The decades following the civil rights and decolonization movements of the sixties and seventies--termed the post-soul era--created new ways to understand the aesthetics of global racial representation. Daphne Lamothe shows that beginning around 1980 and continuing to the present day, Black literature, art, and music resisted the pull of singular and universal notions of racial identity. Developing the idea of "Black aesthetic time"--a multipronged theoretical concept that analyzes the ways race and time collide in the process of cultural production--she assesses Black fiction, poetry, and visual and musical texts by Paule Marshall, Zadie Smith, Tracy K. Smith, Dionne Brand, Toyin Ojih Odutola, and Stromae, among others. Lamothe asks how our understanding of Blackness might expand upon viewing racial representation without borders--or, to use her concept, from the permeable, supple place of Black aesthetic time. Lamothe purposefully focuses on texts told from the vantage point of immigrants, migrants, and city dwellers to conceptualize Blackness as a global phenomenon without assuming the universality or homogeneity of racialized experience. In this new way to analyze Black global art, Lamothe foregrounds migratory subjects poised on thresholds between not only old and new worlds, but old and new selves.
Chapter Eight. Swing Time: Politically Minded with an Individual Soul -- Notes -- Bibliography -- Index -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- Q -- R -- S -- T -- U -- V -- W
Description based upon print version of record.
JSTOR
Keywords: Aesthetics, Black; American literature -- African American authors -- 20th century -- History and criticism; American literature -- African American authors -- 21st century -- History and criticism; English literature -- Black authors -- 20th century -- History and criticism; English literature -- Black authors -- 21st century -- History and criticism; Musicians, Black -- Belgium -- History and criticism; Artists, Black -- United States -- History and criticism; African diaspora; Esthétique noire; Littérature anglaise -- Auteurs noirs -- 20e siècle -- Histoire et critique; Littérature anglaise -- Auteurs noirs -- 21e siècle -- Histoire et critique; Musiciens noirs -- Belgique -- Histoire et critique; Artistes noirs -- États-Unis -- Histoire et critique; Africains -- Pays étrangers.; SOCIAL SCIENCE / Ethnic Studies / American / African American & Black Studies